Freedom of expression on the Internet: from the safe harbour laws to content moderation - Valiente Martínez, Francisco (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2022)
The rise of new technologies has led to a revolution in human communication, which has become global, massively multilateral and essentially digital. Regulating online activity is essential to protect Internet users, as the large multinational companies that own the main social networks design conditions and policies of use that limit the exercise of our fundamental rights, particularly our freedom of expression. The various alternatives for regulating the operation of Internet service providers and achieving a balanced and viable regulatory model at international level is a challenge that cannot be postponed any longer.